Determinants on the choice of telecommunication providers among undergraduates of public universities - Micheal, Tinggi; Shaharudin, Jakpar; Ong, Chee Tiong; Junaid, M. Shaikh (Inderscience Enterprises Ltd., 2014)
The mobile phone is rapidly growing in essentiality in the era of the information technology industry, especially among undergraduates albeit the rising number of competing service providers for mobile phones. A new niche market for this mobile gadget would very soon become overcrowded, thus compelling service providers to continuously be seeking the right mix of determining variables that would make customers buy and stick to their product. The empirical research on six public universities emphasises the decision-making model by Assael (1992), Schiffman and Kanuk (2004), and Engel et al. (1990) as it seeks to evaluate the 4ps (product, promotion, price ad place) and less common antecedents (family, friends and social class) as component of inputs. The findings show that all the factors are contributory variables, with the exception of ‘product factor’, which shows spurious reliability results. However it was found out that price was the most notable determinant.